2013
DOI: 10.1063/1.4803420
|View full text |Cite
|
Sign up to set email alerts
|

Immersion freezing of clay minerals and bacterial ice nuclei

Abstract: The immersion mode ice nucleation efficiency of clay minerals and biological aerosols has been investigated using the AIDA (Aerosol Interaction and Dynamics in the Atmosphere) cloud chamber. Both monodisperse and polydisperse populations of (1) various clay dust samples as well as (2) Snomax ® (a proxy for bacterial ice nucleators) and (3) hematite are examined in the temperature range between-4 ÛC and-35 ÛC. The temperature dependence of ice formation inferred by the INAS (Ice Nucleation Active Surface-Site) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For the WP13 data ξ obs = 0.33 and ξ st = 1/ω obs = 1/0.52 = 1.92. Hiranuma et al (2013) show data for illite in the temperature range of −28 to −33 • C for two rates of cooling in the AIDA chamber. After accounting for sedimentation of the crystals, a shift was found toward colder temperatures by about 1 • C for a factor 8 increase in the rate of cooling, so that ξ obs = 0.48…”
Section: G Vali: Interpretation Of Freezing Nucleation Experimentsmentioning
confidence: 99%
“…For the WP13 data ξ obs = 0.33 and ξ st = 1/ω obs = 1/0.52 = 1.92. Hiranuma et al (2013) show data for illite in the temperature range of −28 to −33 • C for two rates of cooling in the AIDA chamber. After accounting for sedimentation of the crystals, a shift was found toward colder temperatures by about 1 • C for a factor 8 increase in the rate of cooling, so that ξ obs = 0.48…”
Section: G Vali: Interpretation Of Freezing Nucleation Experimentsmentioning
confidence: 99%
“…10 Field studies have identified heterogeneous ice nucleation as the dominant formation mechanism in both ice and mixed-phase cloud formation. 5,11 INPs are rare in the atmosphere, estimated to be 1 in 10 5 to 10 6 particles, 12 which has led to a poor understanding of both their identity and the mechanism by which they nucleate ice. Two major pathways for heterogeneous ice formation are deposition and immersion freezing 13 as illustrated in Figure 1.…”
mentioning
confidence: 99%
“…Heterogeneous ice nucleation occurs at warmer temperatures when ice formation is catalyzed by the presence of INPs . Field studies have identified heterogeneous ice nucleation as the dominant formation mechanism in both ice and mixed-phase cloud formation. , INPs are rare in the atmosphere, estimated to be 1 in 10 5 to 10 6 particles, which has led to a poor understanding of both their identity and the mechanism by which they nucleate ice.…”
mentioning
confidence: 99%
“…Figure 7c > −15 • C while mineral IN dominate at < −15 • C (e.g., Maki et al, 1974;Kieft and Ahmadjian, 1989;DeMott and Prenni, 2010;Atkinson et al, 2013;Hiranuma et al, 2013;Joly et al, 2013;Pummer et al, 2015;Fröhlich-Nowoisky et al, 2016;Kunert et al, 2019;Huang et al, 2021).…”
Section: Ice Nucleation Activitymentioning
confidence: 99%